2014
DOI: 10.1111/tri.12324
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity and safety profile of silibinin in HCV patients with advanced fibrosis after liver transplantation: a randomized clinical trial

Abstract: SummaryResponse to interferon-based therapies in HCV recurrence after liver transplantation (LT) is unsatisfactory, and major safety issues aroused in preliminary experience with boceprevir and telaprevir. As transplant community identified HCV viral clearance as a critical matter, efficacious and safe anti-HCV therapies are awaited. The aim of this study was to assess efficacy and safety of intravenous silibinin monotherapy in patients with established HCV recurrence after LT, nonresponders to pegylated inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 31 publications
(37 reference statements)
4
27
0
Order By: Relevance
“…Twelve liver transplant patients with established HCV recurrence were treated for 14 days with iv-SIL (20 mg/kg/day, i.v.). As previously shown in a larger cohort of patients [ 2 ], on day 14 of treatment, HCV viral load (Fig. 1 ) decreased significantly compared with the pretreatment level (6.38 ± 0.58 vs 4.19 ± 1.25 log 10 IU/ml).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Twelve liver transplant patients with established HCV recurrence were treated for 14 days with iv-SIL (20 mg/kg/day, i.v.). As previously shown in a larger cohort of patients [ 2 ], on day 14 of treatment, HCV viral load (Fig. 1 ) decreased significantly compared with the pretreatment level (6.38 ± 0.58 vs 4.19 ± 1.25 log 10 IU/ml).…”
Section: Resultssupporting
confidence: 81%
“…In vivo and in vitro studies have shown that the anti-HCV effect of Silibinin involves stimulation of toll-like receptor (TLR) 7, interferon regulatory factor 3, and p38 mitogen-activated protein kinase pathways [ 1 ]. The safety and efficacy of Silibinin as anti-viral therapy has been demonstrated in chronic HCV-infected patients and in liver transplant patients with HCV recurrence unresponsive to standard combined therapy with interferon/ribavirin [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…These factors could influence regimen adherence/drug compliance and circumvent the need for intravenous infusion and lessen the requirement for more extensive professional medical care. Importantly, recent clinical studies have indicated favourable outcomes for the inclusion of intravenous silibinin treatment against HCV recurrence and advanced fibrosis in liver transplant patients 38. It has also been considered as a prelude and complementary treatment to DAA therapy against HCV in HIV/HCV-coinfected individuals 39 40.…”
Section: Discussionmentioning
confidence: 99%
“… Arjmand et al, 2020 , Lin et al, 2017 , Li et al, 2011 , Liu et al, 2004 , Liu et al, 2020 , Liu et al, 2019 , Lowe et al, 2017 , Luo et al, 2020 , Maggio and Corsini, 2020 , Magalhães et al, 1985 , Magrone et al, 2020 , Mani et al, 2020 , Mohammed et al, 2020 , Matsuyama et al, 2014 , Mecha et al, 2013 , Menezes‐Rodrigues et al, 2020 , Millet and Whittaker, 2018 , Millet et al, 2016 , Brodkiewicz et al, 2020 , Ming and Yin, 2013 , Nelson et al, 2003 , Mousavizadeh and Ghasemi, 2020 , Nikhat and Fazil, 2020 , O'Keefe et al, 2010 , Panraksa et al, 2017 , Pandey, 2011 , Park et al, 2013 , Park et al, 2017 , Calabrese et al, 2000 , Paris et al, 1994 , Patel et al, 2008 , Peng et al, 2000 , Perwitasari et al, 2015 , Rathinavel et al, 2020 , Rendina et al, 2014 , Cameron and Castro, 2001 , Rothan et al, 2019 , Roh, 2012 , Ryu et al, 2010b , Saavedra, 2020 , Sadaie et al, 2004 , Sahebkar et al, 2016 , Shaito et al, 2020 , Shao et al, 2013 , Shen et al, 1996 , Shin and Seong, 2017 , Shin et al, 2013 , Song and Choi, 2011 , Su et al, 2020 , Su et al, 2020 , Cao et al, 2013 , Tyagi et al, 2016 , Utsunomiya et al, 1997 , Vankadari and Wilce, 2020 , Wang et al, 2011 , Cao et al, 2013 ...…”
Section: Uncited Referencesmentioning
confidence: 99%